Design and prototyping of a novel composite architecture for a widebody landing gear bay. (2021) - Viscardi, M.; Arena, M.; Cerreta, P.; Iaccarino, P.
Abstract: Composite materials may reduce the final weight of the aircraft structural components, in addition to improve fatigue performance and corrosion resistance. In order to achieve the optimization of air transport systems, making them increasingly sustainable, the structural design must be surely reviewed, starting to follow the "composite thinking" philosophy. The present research provides some relevant outcomes concerning the design of a composite sample for the main landing gear bay of a large commercial airplane (EASA CS25 category), within ITEMB (InTEgrated Full Composite Main landing gear Bay Concept) project, a program of Clean Sky 2 EU research framework. The most ambitious goal is to develop a new generation of Lower Center Fuselage (LCF) with an innovative integrated landing system in the fuselage, which is considered the next frontier in the development of landing systems for medium-haul aircraft, such as the Airbus A320 aircraft family. The development of a different architecture, with the landing gear integrated within the related fuselage bay, could lead to a simplification of the whole sub-assembly with potential advantage in terms of construction and assembly times. Final target of the project is the manufacturing of an innovative monolithic composite structure that will replace the actual configuration (a mixed structure of metal and composite sub-assemblies) reducing or actually removing all the cost of assembly and increasing the production rate. This paper presents the main results of the work, introducing the main processing steps and prototype results; in the last part of the work, also some experimental test on significant element are introduced as first assessment of the technology readiness level that has been achieved.